Effects of Ellagic Acid Supplementation on Jejunal Morphology, Digestive Enzyme Activities, Antioxidant Capacity, and Microbiota in Mice - Xu, Qiuying; Shen, Mingkang; Han, Yuxin; Diao, Hui (Frontiers in Microbiology, 2021)
Ellagic acid (EA), as a plant polyphenol, mainly found in nuts and fruits, exhibits various biological effects. However, the effects of EA on intestinal development and antioxidant capacity are poorly reported. Toward these ends, this work was designed to evaluate the influences of EA supplementation on the morphology, digestive enzyme activities, and anti-oxidant capacity of jejunum in C57BL/6J mice. A total of 24 mice were randomly assigned to three treatments: control group (received a standard pellet diet), 0.1% EA group (received a standard pellet diet plus 0.1% EA) and 0.3% EA group (received a standard pellet diet plus 0.3% EA). The mice were killed at the end of the experimental period and jejunum samples were collected. The results showed that 0.3% EA supplementation improved (P < 0.05) the final body weight (BW) and average daily gain (ADG) in mice, and increased (P < 0.05) jejunal villus height compared with the CON group. Besides, the jejunal lactase and sucrase activities were higher (P < 0.05) in the 0.1% EA and 0.3% EA group and alkaline phosphatase activity were higher (P < 0.05) in the 0.3% EA group than those in the CON group. While administration of EA increased (P < 0.05) the superoxide dismutase (SOD) and catalase (CAT) activities in jejunum, it decreased (P < 0.05) the malonaldehyde (MDA) content in these samples when compared to the CON group. Moreover, the jejunal mRNA expressions of nuclear factor-E2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) were increased (P < 0.05) in mice fed the 0.3% EA-supplemented diet in comparison to the control. The quantity of E. coli decreased (P < 0.05), while the quantity of Lactobacillu increased (P < 0.05) in the 0.3% EA group compared with the CON group. In general, our findings indicate that administration of EA can promote intestine development and enhance antioxidant capacity.